Kit de baixo custo para avaliação da potabilidade da água em zonas rurais - Luiz Gomes Junior (2010)
This research aimed to produce a kit for evaluating water quality, of simple functioning and low cost of confection, so that the producer by himself can carry through the frequent monitoring by means of physical-chemical analyses of the water, for families of rural community from Planalto, in Montes Claros, semi-arid region of Minas Gerais. The alternative kit was developed at laboratories of the UFMG - Universidade Federal de Minas Gerais, that made possible the comparison of its results with the ones from conventional methods. Tests for analyses of physical-chemical parameters were carried out, in laboratory, with water samples, by conventional means and by the alternative kit, after that it was tested the kits efetiveness in community from Planalto. This kit made possible to examine the water quality quickly and in loco, decreasing the risk that population placed in region of similar characteristics to rural community from Planalto consummates water of low quality.